Comparison of Nutritional Content of Spinach (Amaranthus gangeticus L.) Cultivated Hydroponically and Non-Hydroponically - Fevria, Resti; Alicia Farma, Siska; Vauzia; Edwin, Edwin; Purnamasari, Devi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
The objectives of this study to determine the comparison of the nutritional content of spinach cultivated hydroponically and non-hydroponically, especially the content of Vitamin C. This research was conducted at the Wire House Biology Laboratory of Padang State University in May - July 2020. This research is a descriptive study. The analysis was carried out Spinach Nutrition. Hydroponic spinach samples were obtained from the Hydroponic Community of West Sumatra in Alai Padang, while the non-hydroponic samples were purchased at Pasar Raya Padang, the analysis of vitamin C content was carried out by the Spectrophotometric Method. From the research that has been done, it is found that the average content of hydroponic spinach vitamin C is 1.45 ppm and non-hydroponic 1.60 ppm. The conclusion of the research is that the content of Vitamin C in hydroponic cultivated spinach is lower than that of spinach cultivated non-hydroponically.